Differences and discriminatory power of water polo game-related statistics in men in international championships and their relationship with the phase of the competition - Escalante, Y.; Saavedra, J. M.; Tella, V.; Mansilla, M.; Garcia-Hermoso, A.; Dominguez, A. M. (The Journal of Strength and Conditioning Research, 2013)
The aims of this study were (a) to compare water polo game-related statistics by context (winning and losing teams) and phase (preliminary, classification, and semifinal/bronze medal/gold medal), and (b) identify characteristics that discriminate performances for each phase. The game-related statistics of the 230 men's matches played in World Championships (2007, 2009, and 2011) and European Championships (2008 and 2010) were analyzed. Differences between contexts (winning or losing teams) in each phase (preliminary, classification, and semifinal/bronze medal/gold medal) were determined using the chi-squared statistic, also calculating the effect sizes of the differences. A discriminant analysis was then performed after the sample-splitting method according to context (winning and losing teams) in each of the 3 phases. It was found that the game-related statistics differentiate the winning from the losing teams in each phase of an international championship. The differentiating variables are both offensive and defensive, including action shots, sprints, goalkeeper-blocked shots, and goalkeeper-blocked action shots. However, the number of discriminatory variables decreases as the phase becomes more demanding and the teams become more equally matched. The discriminant analysis showed the game-related statistics to discriminate performance in all phases (preliminary, classificatory, and semifinal/bronze medal/gold medal phase) with high percentages (91, 90, and 73%, respectively). Again, the model selected both defensive and offensive variables.